2018
DOI: 10.3390/nu10030261
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Approach to Recurrent or Chronic Hyperkalaemia in Patients with Decreased Kidney Function

Abstract: Whereas the adequate intake of potassium is relatively high in healthy adults, i.e., 4.7 g per day, a dietary potassium restriction of usually less than 3 g per day is recommended in the management of patients with reduced kidney function, especially those who tend to develop hyperkalaemia including patients who are treated with angiotensin pathway modulators. Most potassium-rich foods are considered heart-healthy nutrients with high fibre, high anti-oxidant vitamins and high alkali content such as fresh fruit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
151
1
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(161 citation statements)
references
References 41 publications
2
151
1
7
Order By: Relevance
“…Given the high prevalence of hyperkalemia and its significant association with increased mortality in patients with CKD, it is important to recognize the potential impact of constipation on hyperkalemia management in this population. 91 Dietary potassium is absorbed mostly in the duodenum and jejunum and the net intestinal potassium absorption is approximately 90%. Under physiologic circumstances, intestinal potassium excretion is quite constant at approximately 10 mmol/d, with a maximum level of 15 to 20 mmol/d 91 ; however, when the kidneys are unable to excrete the dietary potassium load (i.e., oliguria/anuria), the gut becomes especially important for maintaining potassium balance.…”
Section: Constipation and Hyperkalemia In Ckdmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the high prevalence of hyperkalemia and its significant association with increased mortality in patients with CKD, it is important to recognize the potential impact of constipation on hyperkalemia management in this population. 91 Dietary potassium is absorbed mostly in the duodenum and jejunum and the net intestinal potassium absorption is approximately 90%. Under physiologic circumstances, intestinal potassium excretion is quite constant at approximately 10 mmol/d, with a maximum level of 15 to 20 mmol/d 91 ; however, when the kidneys are unable to excrete the dietary potassium load (i.e., oliguria/anuria), the gut becomes especially important for maintaining potassium balance.…”
Section: Constipation and Hyperkalemia In Ckdmentioning
confidence: 99%
“…91 Dietary potassium is absorbed mostly in the duodenum and jejunum and the net intestinal potassium absorption is approximately 90%. Under physiologic circumstances, intestinal potassium excretion is quite constant at approximately 10 mmol/d, with a maximum level of 15 to 20 mmol/d 91 ; however, when the kidneys are unable to excrete the dietary potassium load (i.e., oliguria/anuria), the gut becomes especially important for maintaining potassium balance. 92 A series of potassium balance studies have demonstrated that potassium excretion in stool was 3 times higher in HD patients compared with healthy controls, reaching approximately 80% of dietary potassium (up to 3000 mg/d) for some HD patients.…”
Section: Constipation and Hyperkalemia In Ckdmentioning
confidence: 99%
“…15,19,40 This section discusses the clinical implications of addressing the effects of hyperkalemia management on diet, RAAS inhibitor therapy, and hemodialysis and reviews research with new K þ -binding agents that may 41,42 However, in patients at risk for hyperkalemiadsuch as those who have late stages of CKDdhigh dietary K þ presents a clinical challenge. 19,42 Dietary K þ restriction (<3 g/d) is recommended in patients at risk for hyperkalemia but should be individualized because it can lead to patients not receiving the benefits of a heart-healthy diet [43][44][45] (Table 3). 44,46,47 Appropriate dietary counseling is important in patients with CKD with or at risk of hyperkalemia but can be challenging in clinical practice without dedicated resources.…”
Section: Hyperkalemia and Challenges For Ckd Managementmentioning
confidence: 99%
“…Furthermore, greater dietary potassium intake was associated with higher mortality even after adjustment for serum potassium level in dialysis patients (8). Thus, dialysis patients should consume fruit and vegetables following cautious dietary advice (9). Healthy dietary patterns but not fruit and vegetables should be tested in dialysis patients.…”
Section: Dear Editormentioning
confidence: 99%